Strong coupling in hybrid metal–dielectric nanoresonators. (28th March 2017) - Decker, M.; Pertsch, T.; Staude, I.
Abstract : We study resonant photonic–plasmonic coupling between a gold dipole nanoantenna and a silicon nanodisc supporting electric and magnetic dipolar Mie-type resonances. Specifically, we consider two different cases for the mode structure of the silicon nanodisc, namely spectrally separate and spectrally matching electric and magnetic dipolar Mie-type resonances. In the latter case, the dielectric nanoparticle scatters the far fields of a unidirectional Huygens' source. Our results reveal an anticrossing of the plasmonic dipole resonance and the magnetic Mie-type dipole resonance of the silicon nanodisc, accompanied by a clear signature of photonic–plasmonic mode hybridization in the corresponding mode profiles. These characteristics show that strong coupling is established between the two different resonant systems in the hybrid nanostructure. Furthermore, our results demonstrate that in comparison with purely metallic or dielectric nanostructures, hybrid metal–dielectric nanoresonators offer higher flexibility in tailoring the fractions of light which are transmitted, absorbed and reflected by the nanostructure over a broad range of parameters without changing its material composition. As a special case, highly asymmetric reflection and absorption properties can be achieved. This article is part of the themed issue 'New horizons for nanophotonics'.